-(z+7)+(2z+1)=-4(z+1)

Simple and best practice solution for -(z+7)+(2z+1)=-4(z+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(z+7)+(2z+1)=-4(z+1) equation:


Simplifying
-1(z + 7) + (2z + 1) = -4(z + 1)

Reorder the terms:
-1(7 + z) + (2z + 1) = -4(z + 1)
(7 * -1 + z * -1) + (2z + 1) = -4(z + 1)
(-7 + -1z) + (2z + 1) = -4(z + 1)

Reorder the terms:
-7 + -1z + (1 + 2z) = -4(z + 1)

Remove parenthesis around (1 + 2z)
-7 + -1z + 1 + 2z = -4(z + 1)

Reorder the terms:
-7 + 1 + -1z + 2z = -4(z + 1)

Combine like terms: -7 + 1 = -6
-6 + -1z + 2z = -4(z + 1)

Combine like terms: -1z + 2z = 1z
-6 + 1z = -4(z + 1)

Reorder the terms:
-6 + 1z = -4(1 + z)
-6 + 1z = (1 * -4 + z * -4)
-6 + 1z = (-4 + -4z)

Solving
-6 + 1z = -4 + -4z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '4z' to each side of the equation.
-6 + 1z + 4z = -4 + -4z + 4z

Combine like terms: 1z + 4z = 5z
-6 + 5z = -4 + -4z + 4z

Combine like terms: -4z + 4z = 0
-6 + 5z = -4 + 0
-6 + 5z = -4

Add '6' to each side of the equation.
-6 + 6 + 5z = -4 + 6

Combine like terms: -6 + 6 = 0
0 + 5z = -4 + 6
5z = -4 + 6

Combine like terms: -4 + 6 = 2
5z = 2

Divide each side by '5'.
z = 0.4

Simplifying
z = 0.4

See similar equations:

| x+6+2x-3=90+45 | | 24x^2y^3+36x^4-72x^3y^2=0 | | 22y+18-15y= | | 5(3z-1)-2(z+2)=8(z+1) | | 4n+7-2n=3n-3 | | 60x=50(x+1) | | 2x^2-16x=7 | | 24y= | | x^2-7xy+6y^2=equation | | 2x^2+12x=12 | | 12x-5=3x+45 | | 180-x=279 | | 180-x=179 | | 160-x=88 | | ln(x)=0.0023 | | 8p^3-343/9 | | 6xwhat=96 | | 4x^2-1x-6=0 | | (1+x^4)dy+x(4y^2+1)dx=0 | | 646.8+-1.2y= | | 5.76X^2+2.86X-1.35=8 | | 10+y=10+0.5y | | 7m^2-4m=3m*(m-7/2) | | 3m*(m-7/2) | | 6x-sqrtx=12 | | 4/5x-10=54 | | f(x)=[x-3] | | 91+19m=376 | | 15x+45x-4y= | | 34n-104=338 | | 6m+6.75=63.75 | | 5x^2-6x=4x^2+6x-13 |

Equations solver categories